A Randomized Controlled Trial of Listening Visits for Mothers of Hospitalized Newborns. Issue 3 (21st May 2023) - Segre, Lisa S.; McCabe, Jennifer E.; Davila, Rebecca Chuffo; Carter, Cheryl; O'Hara, Michael W.; Arndt, Stephan
Abstract : Background: Emotional distress is frequently experienced by mothers whose newborns are hospitalized in a neonatal intensive care unit (NICU). Among these women, there is a critical need for emotional support conveniently delivered at the newborn's point of care by a trusted and medically knowledgeable professional: a NICU nurse. One promising way to enhance in situ delivery of emotional care is to have a NICU nurse provide Listening Visits (LVs), a brief support intervention developed expressly for delivery by nurses to depressed postpartum women. Objectives: This trial assessed the feasibility of having NICU nurses deliver LVs to emotionally distressed mothers of hospitalized newborns and compared depression outcomes in a small sample of participants randomized to LVs or usual care (UC). Methods: In this pilot randomized controlled trial, emotionally distressed mothers of hospitalized newborns were randomized to receive up to six LVs from a NICU nurse or UC from a NICU social worker. To assess change in depression symptoms, women were invited to complete the Inventory of Depression and Anxiety Symptoms–General Depression Scale at enrollment and 4 and 8 weeks post-enrollment. Results: Depression symptoms declined over time for both groups, with no difference between the two groups. A post hoc analysis of reliable change found higher rates of improvement at the 4-week assessment among recipients of LVs than UC. Discussion: NICU nurses successfully implemented LVs during this trial. Depression symptom scores did not significantly differ in the two groups posttreatment or at follow-up. Nevertheless, post hoc analyses indicated comparatively higher rates of clinical improvement immediately after LVs, suggesting the intervention can reduce maternal depression early on when women are most distressed.